Integrating advanced computer-aided design, manufacturing, and numerical control [ principles and implementations - Xu, Xun , 1959- (Information Science Reference, 2009)
"This book presents basic principles of geometric modelling while featuring contemporary industrial case studies"--Provided by publisher